Ein differenzierter Blick auf einen Euro-Austritt Griechenlands - Stergios Xouridas (Wirtschaftsdienst, 2012)
Die Situation der griechischen Wirtschaft spitzt sich aktuell dramatisch zu. Eine Besserung der Lage setzt einen wettbewerbsfähigen Exportsektor voraus. Dabei wäre die Wiedereinführung der Drachme eine Option, die der Autor allerdings für schwer durchführbar hält. – – Since the large current account defi cit in Greece has become a source of concern regarding its sustainability, an increasing number of economists advocate the reintroduction of a devalued Greek drachma in order to improve the competitiveness of the Greek economy and help boost exports. This paper offers a contrasting perspective and puts the positive aspects of the reintroduction of the drachma in the context of legal and economic repercussions following the devaluation. The paper concludes that it is advisable for Greece to stay within the eurozone and counterbalance the ongoing austerity measures with investments to increase the competitiveness of its economy.
Keywords: H63; E42; 330; Wirtschaftslage; Zahlungsbilanzgleichgewicht; Internationaler Wettbewerb; Wirtschaftliche Anpassung; Währungsumstellung; Wirkungsanalyse; Griechenland